Effect of Walking Exercise with Breathing Control on the Degree of Shortness of Breath, Anxiety, and Depression in COPD: A Systematic Review - Orita Satria; Dewi Elizadiani Suza; Mula Tarigan (Jurnal Respirasi, 2022)
Introduction: Chronic obstructive pulmonary disease (COPD) is a high disease burden and negatively impacts the bio-psycho-social well-being of patients, such as anxiety, depression, and shortness of breath. Anxiety and depression can increase morbidity and worsen the condition and health status of the patient. This systematic review aimed to analyze the effect of walking exercises with breathing control on the degree of shortness of breath, anxiety, and depression in COPD patients. Methods: The data sources were taken from EBSCO, PubMed, and ProQuest using related keywords. Articles were selected using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) diagram method. Results: Ten articles in this systematic review obtained three intervention categories: 1) intervention combined walking exercises with breathing control can be performed 30 minutes per session 2-3 times a week; 2) walking exercise intervention is performed thrice a week for 30-45 minutes per session; 3) breathing control exercise intervention is performed 10-30 minutes with a duration of 2 times a day in the morning and night or can be performed three times a week. Those three intervention categories significantly reduced the degree of shortness of breath, anxiety, and depression in COPD patients. Conclusion: Findings from this systematic review suggest that walking exercise intervention in COPD patients can help reduce the degree of shortness of breath, anxiety, and depression.